The impact of training on empowering rural women in Latakia Governorate - دالي, رغد (Submission and Review of Research -Biological Sciences Series, 2025)
The study aims to investigate the role of training in empowering rural women economically and socially in Latakia Governorate. A purposive sample of 136 rural women was selected, and data were collected using a questionnaire through face-to-face interviews. The study adopted a descriptive-analytical approach to analyze responses using the five-point Likert scale, frequency tables, means, standard deviations, and percentages. Hypotheses were tested using Pearson’s correlation coefficient and one-way ANOVA. Results showed a high level of training (mean = 3.77), a moderate level of economic empowerment (mean = 3.21), and a high level of social empowerment (mean = 3.83), indicating a statistically significant relationship between training and both economic and social empowerment. The findings also revealed statistically significant differences based on educational level, where educated women with good income and creative skills showed higher empowerment levels. This highlights the importance of investing in training programs for rural women to enhance their economic and social status.